2022
DOI: 10.17749/2077-8333/epi.par.con.2022.121
|View full text |Cite
|
Sign up to set email alerts
|

Indigenous practices for management of epilepsy by traditional healers in South Africa

Abstract: Objective: to determine the indigenous practices that are used to manage epilepsy in South Africa rural communities.Material and methods. A qualitative, ethnographic technique that was exploratory and descriptive was used. Purposive and snowball sampling were used to select a group of 17 traditional healers for in-depth interviews at their homes. The data were analysed through the open coding data analysis method.Results. The traditional healers had different perspectives on the origins and treatment plans of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Cultural beliefs and superstitions significantly influence the perception of epilepsy in many rural communities [8,34,37,43,44]. Some cultures attribute seizures to spiritual or supernatural causes, associating them with curses, evil spirits, or divine punishment.…”
Section: Stigma and Its Impact 21 Stigma And Misconceptions About Epi...mentioning
confidence: 99%
“…Cultural beliefs and superstitions significantly influence the perception of epilepsy in many rural communities [8,34,37,43,44]. Some cultures attribute seizures to spiritual or supernatural causes, associating them with curses, evil spirits, or divine punishment.…”
Section: Stigma and Its Impact 21 Stigma And Misconceptions About Epi...mentioning
confidence: 99%
“…Subsequently, family members and caregivers’ lives are altered and, to some degree, burdened by living with or caring for a person with epilepsy [ 3 , 4 ]. This may influence practices toward PLWE, especially during a seizure, because it was found that about 80% of Africans consult traditional healers and engage in traditional rituals in an attempt to stop the seizure or cure epilepsy [ 5 ]. Some of these rituals include herb steaming and using gonono (Black coloured insect) and plant mixtures [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…This may influence practices toward PLWE, especially during a seizure, because it was found that about 80% of Africans consult traditional healers and engage in traditional rituals in an attempt to stop the seizure or cure epilepsy [ 5 ]. Some of these rituals include herb steaming and using gonono (Black coloured insect) and plant mixtures [ 5 ]. This supports the idea that there is a need to provide informational support to family members and caregivers [ 6 ].…”
Section: Introductionmentioning
confidence: 99%